PERGESERAN NILAI-NILAI ISLAM DALAM CERITA ALADDIN: PERBANDINGAN â€œARABIAN NIGHTSâ€ DAN FILM ANIMASI DISNEY - Rahayu, Mundi; Abdullah, Irwan; Udasmoro, Wening (UIN Maulana Malik Ibrahim Malang, 2015)
This study compares the folktale â€œThe Story of Aladdin and the Wonderful Lampâ€ from the Arabian Nights, and the animated film produced by Walt Disney Feature Animation under the title â€œAladdinâ€ (1992). The story of Disneyâ€™s animated film â€œAladdinâ€ is based on the â€œThe Story of Aladdin and the Wonderful Lamp.â€ The comparison of the two is focused on the aspect of Islamic values, its shifts and changes in the animated film Aladdin. The study applies Faircloughâ€™s Critical Discourse Analysis, by applying the three stages of analysis.Â The first level is micro level, on the language practice. In the second level, mezo level, discusses the discourse practice that covers the intertextuality that explore the production and consumption of text as the reference in delivering the ideas. In the third level, macro level, it interprets the social context of particular events. The finding shows that there is a change of discourse of Islamic value which is strongly expressed in the origiinal Aladdin story of â€œArabian Nightsâ€ especiallly the important role of family. On the other hand, in the animated film Aladdin, remove the discourse of Islamic value and change it into the discourse of freedom.Â Artikel ini membandingkan dua cerita Aladdin yang diterjemahkan ke dalam bahasa Inggris menjadi Arabian Nights dengan judul cerita â€œThe Story of Aladdin and the Wonderful Lamp,â€ dengan film animasi produksi Walt Disney Feature Animation dengan judul â€œAladdinâ€ (1992). Cerita Aladdin dalam film animasi ini didasarkan pada ceritaâ€œThe Story of Aladdin and the Wonderful Lamp.â€ Perbandingan ini difokuskan pada aspek nilai-nilai Islam, pergeseran dan perubahan yang terjadi pada film animasi Aladdin. Studi ini menerapkan Analisis Wacana Kritis Fairclough dengan menerapkan tiga tingkatan analisis. Tingkatan pertama adalah analisis mikro atau aspek bahasa. Pada tingkatan kedua adalah tingkatan mezo, yang menganalisis praktik wacana yang mencakup intertekstualitas yang mengeksplorasi produksi dan konsumsi teks referensi atas suatu gagasan. Pada tataran ketiga, tataran makro analisis difokuskan pada konteks sosial dari suatu peristiwa naratif tertentu. Hasil analisis menunjukkan bahwa ada pergeseran dan perubahan nilai-nilai Islam yang dalam cerita Aladdin. Dalam â€œArabian Nightsâ€ cerita Aladdin sangat menonjolkan wacana nilai Islam terutama dalam hal peran penting keluarga, sedangkan dalam film animasi Aladdin wacana yang menonjol adalah nilai kebebasan.